Vedolizumab may be an effective option for the treatment of postoperative recurrence of Crohn's disease. Issue 5 (May 2022) - Macaluso, Fabio Salvatore; Cappello, Maria; Crispino, Federica; Grova, Mauro; Privitera, Antonino Carlo; Piccillo, Giovita; Magnano, Antonio; Ferracane, Concetta; Belluardo, Nunzio; Giangreco, Emiliano; Fries, Walter; Viola, Anna; et al.
Abstract: Background: The role of Vedolizumab (VDZ) as therapeutic option for the postoperative recurrence of Crohn's disease (CD) following ileocolonic resection is unknown. Aims: To assess the effectiveness of VDZ in this setting. Methods: All consecutive CD patients with a baseline colonoscopy at 6–12 months from the ileocolonic resection showing postoperative recurrence (Rutgeerts score ≥i2) and treated with VDZ after the baseline colonoscopy were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). The primary outcome was endoscopic success, assessed at the first colonoscopy following initiation of VDZ and defined as reduction of at least one point of Rutgeerts score. The secondary outcome was clinical failure, assessed at one year and at the end of follow-up. Results: Fifty-eight patients were included (mean follow-up: 24.8 ± 13.1 months). Endoscopic success was reported in 47.6% of patients. Clinical failure was reported in 19.0% of patients at one year, and in 32.8% of patients at the end of follow-up. A new resection was required in 7 patients (12.1%). Conclusions: VDZ may be an effective option for the treatment of postoperative recurrence of CD.